Economic and legal bases of the Carpathian Euroregion development during the COVID-19 pandemic : Hungary, Slovakia, Poland, Ukraine - Ruslan V. Khusainov; Anton Lisnik; Monika Zatrochová; Alla M. Babiuk; Kostiantyn Ye. Mashkov (Journal of Innovation and Entrepreneurship, 2023)
The article dwells upon the history of the Carpathian Euroregion as the form of a cross-border cooperation. The peculiarities of the economic development of the Carpathian Euroregion before the COVID-19 pandemic were considered. The main ways of obtaining financial resources for the development of the Euroregion economy were identified. The structure of the Carpathian Euroregion and the system of normative legal acts regulating the activity of this association were analyzed. The main consequences and impact of the COVID-19 pandemic on the economic development of the Carpathian Euroregion were identified. Priority measures and activities for tourism development in the Carpathian Euroregion were discussed. The expediency of creating a tourist brand of the Euroregion and the need to promote tourism in the Euroregion at the international level were argued. The main international projects and programs of the Carpathian Euroregion regarding the cooperation between the states of the EU were studied. Proposals were made to improve the investment attractiveness of the Carpathian Euroregion and to overcome the consequences of the pandemic. The need to create a separate authority that will operate independently and ensure active communication in the Euroregion was established. It will also help find new sources of financial resources, develop a set of measures to support small and medium businesses, connections between the territories of the Euroregion and ensure an effective border and customs regime in the Carpathian Euroregion.
Keywords: 650; Pandemic; Economic development; Cross-border cooperation; Euroregion; Tourism